Preterm Birth in Assisted Reproductive Technology: An Analysis of More Than 20,000 Singleton Newborns - Bu, Zhiqin; Zhang, Jiaxin; Hu, Linli; Sun, Yingpu (Frontiers in Endocrinology, 2020)
Background: Several studies have shown that newborns conceived through the ART procedures were associated with an increased incidence of preterm delivery compared to those conceived spontaneously regardless of the type of ART procedure. The aim of the study was to explore risk factors for preterm birth (PTB) in assisted reproductive technology. Method: In this single center retrospective cohort study, a total of 23,111 singleton newborns from January 2010 to December 2018 were included. The primary outcome in this study was preterm birth, defined as live birth before 37 weeks’ gestation. Result: In the 23,111 pregnancies, the incidence of PTB was 7.13%. In multivariate logistic regression analysis model, BMI was an independent predictor for PTB (OR=1.05, 95%CI: 1.03-1.07; P=0.00 in IVF/ICSI cycles; OR=1.08, 95%CI: 1.03-1.12; P=0.00 in IUI cycles). Also, another independent predictor in ART was male newborns (OR=1.27, 95%CI: 1.14-1.41; P=0.00 in IVF/ICSI cycles; OR=1.60, 95%CI: 1.17-2.18; P=0.00 in IUI cycles). In IVF/ICSI cycles, PTB was significantly higher in patients with advanced age (9.56% in ≥ 38 years old), and in patients with a history of cesarean section (10.39%). In addition, Blastocyst transfer, and frozen thawed transfer were also risk factor for PTB as compared with cleavage transfer, and fresh transfer, respectively. Moreover, in frozen thawed transfer cycles, stimulated protocol (estrogen-progesterone) increased PTB as compared with natural protocol (OR=1.33, 95%CI: 1.12-1.59; P=0.00). This situation was similar in IUI cycles as stimulated protocol also increased PTB when compared with natural protocol (OR=1.72, 95%CI: 1.19-2.48; P=0.00). Conclusion: Body mass index (BMI), delivery with male newborn, as well as stimulated protocols, were independent risk factors for PTB in both IVF/ICSI and IUI treatment cycles. In IVF/ICSI cycles, independent risk factors also included maternal, history of cesarean section, frozen thawed transfer, and blastocyst transfer.